The Encyclopedia of Migrants: the intimate and individual dimension of migration stories (interview with Filipa Bolotinha) - Carvalho, Ana (2017)
The Encyclopedia of Migrants is an international project (2014-2017) supported by the Erasmus+ programme. It is based on a network of partner cities on the Atlantic coast (Brest, Rennes, Nantes, Gijón, Porto, Lisbon, Cadiz and Gibraltar), involving eight partners with different profiles (associations, universities, museums, etc.) in France, Spain, Portugal and Gibraltar. The project is coordinated by the French organization L’âge de la Tortue, which works in the visual arts field. The initiative has an artistic and experimental dimension and was originally designed by Paloma Fernández Sobrinho, with the aim to create an encyclopedia in paper version and in digital version with approximately 400 testimonies made by migrants. The Encyclopedia format (a monumental, multi-volume, leather-bound artist book) was chosen in this case in order to disseminate non-scientific knowledge, resulting from life experiences, with all the subjectivity that this involves. The main idea was to gather diverse testimonies of migrants that could be the source of a new knowledge, based on the intimate and the individual. In 2017, publishing sensitive content in the form of an encyclopedia, by means of a popular and contributory initiative, is an artistic and political act.